New multi-material formulations for vat-photopolymerisation and their application in manufacturing ocular implants - Konta, Andrea Alice (2022)
Additive Manufacturing (AM), often referred to as 3D printing, encompasses a series of processes that build structures in an additive fashion, layer by layer. This is usually possible by translating a 3D computer-aided design (CAD) into a standard tessellation language (STL) file that is then directly manufactured into a physical structure. The process that manufactures structures illuminating liquid photosensitive resins with a light source is called vat-photopolymerisation. From the different vat-photopolymerisation techniques, two-photon polymerisation is the technique that allows micro- and nano-printing at the highest resolution. Besides high resolution, it also offers the possibility of manufacturing complex structures without need for support. And it also allows to select degrees of porosity, defined shapes, or intricate topologies. These features had made the technique attractive for several applications like microfluidics, metamaterials, cell culture, or drug delivery.